Animação experimental: da definição da linguagem à arte - Oliveira, Thais Caroline de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Experimental animation emerges as a response to the industrialization of animated films, and is characterized by an audiovisual production made entirely experimentally and out of commercial production. In this research three experimental animations are analyzed: Begone Dull Care (1949) by Norman McLaren (1914-1987) and Evelyn Lambart (1914-1999), Scientific Friction (1959) by Stan Vanderbeek (1927 - 1984) and Darkness, Light, Darkness. (1989) by Jan Svankmajer (1934-). The objective of this analysis was to try to delimit what is exactly an experimental animation, and how it is characterized. With these definitions and characteristics we also sought to bring an approach to the language of artistic production through modernist movements such as Dadaism, Surrealism and Abstractionism

A animação experimental surge como uma resposta à industrialização dos filmes animados, sendo caracterizada por uma produção audiovisual feita de forma totalmente experimental e fora da produção comercial. Nesta pesquisa são analisadas três animações experimentais sendo elas: Begone Dull Care (1949) de Norman McLaren (1914-1987) e Evelyn Lambart (1914-1999), Fricção Científica (1959) de Stan Vanderbeek (1927 - 1984) e Darkness, Light, Darkness. (1989) de Jan Svankmajer (1934-). O objetivo desta análise foi o de tentar delimitar o que é exatamente uma animação experimental, e como esta se caracteriza. Com estas definições e características buscou-se também trazer uma aproximação com a linguagem da produção artística através dos movimentos modernistas como o Dadaísmo, o Surrealismo e o Abstracionismo
Keywords: Arte abstrata; Dadaísmo; Surrealismo; Arts